Employing Chromebooks in English Language Learning (ELL) at Junior High School: An Indepth Analysis - Hartati, Aty; Firdaus, Masagus (Indonesian Research Journal on Education, 2025)
English  is the most widely used language in the world and represents a continuous process to develop students’ communication skills, both spoken and written. The implementation of English learning requires supporting tools such as Chromebooks. The use of Chromebooks as cloud-based digital devices greatly supports this learning process, as it enables access to various learning resources, supporting applications, and interactive activities. The aim of this research is to examine theories closely related to the use of Chromebooks in English learning at the junior high school level. Planning the subjects to be covered, locating pertinent literature sources, and gathering information from those sources to use as references in the discussion and conclusion are the steps involved in carrying out this research.